Yes!

P=IV

V=IR

So first we want them both in V= form. one of them already is, so let's get the other on

P=IV (divide I from both sides) you get

P/I =V

and just flip it around

V=P/I

now you have to equations in V= form. Now how do you get V^2 from V.

well V^2 is just VxV. So multiply the two V's

VxV= (P/I)(IR)

now simplify

**V^2 =PR**

-----------------------------------------------------------------------------------------------------------------------------

and this is not important to answering the question but just to make sure, let's show that P=IV and V=IR can be written as P=I^2R

P=IV

V=IR

well this is true because so you replace the first V with the Second V

P=I(IR)

P=I^2R

---------------------------------------------------------------------------------

So in conclusion. We can go from P=I^2R to V^2=PR by using the two formulas V=IR and P=IV

Edited by _ConcreteRose_ - Dec 24 2013 at 3:14am